Developing Skills for Children with Special Needs at Waraqil Jannah As-Sunah Foundation - Fitria Nora; Irwandi Irwandi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The talent possessed is one of the main assets for the child when he is directly involved in the community. This activity in addition to making the children independent can also improve welfare, especially in improving the economy. After they finish later. The SLB Waraqil Jannah Nagari Paninjauan Kabupaten Tanah Datar Regency provides employment opportunities for them. The type of research used is field research with qualitative research methods. This research was conducted at the Waraqil Jannah As-Sunnah Nagari Paninjauan Foundation, Tanah Datar Regency using interview instruments, documentation using mobile phones, books and pens. In this study, the source of the data obtained is the source of primary data and secondary data. While the data analysis technique used was data reduction, presentation and conclusion drawing and to check the validity of the data, the researchers used source triangulation and technique triangulation, and time. Based on the research findings, the authors found that the empowerment programs at the SLB Waraqil Jannah Nagari Paninjauan Kabupaten Tanah Datar Regency such as painting, embroidery, sewing, catering, vocational, wood crafts, art flower arrangement, paving blocks, workshops, sports are very helpful for children with needs. Apart from being independent, it can also improve the economy.